The New Encyclopedia of Southern Culture : Volume 12: Music - Abadie, Ann J.; Thomas, James G., Jr; Wilson, Charles Reagan; Malone, Bill C. (Book collections on Project MUSE., 2008)
Southern music has flourished as a meeting ground for the traditions of West African and European peoples, leading to the evolution of various traditional folk genres, bluegrass, country, jazz, gospel, rock, blues, and southern hip-hop. This volume in The New Encyclopedia of Southern Culture celebrates an essential element of southern life and makes available a stand-alone reference to the music and music makers of the American South.--description provided by publisher.